2002
DOI: 10.1074/jbc.m205746200
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray Crystallographic Structure ofEscherichia coli Branching Enzyme

Abstract: Branching enzyme catalyzes the formation of ␣-1,6 branch points in either glycogen or starch. We report the 2.3-Å crystal structure of glycogen branching enzyme from Escherichia coli. The enzyme consists of three major domains, an NH 2 -terminal seven-stranded ␤-sandwich domain, a COOH-terminal domain, and a central ␣/␤-barrel domain containing the enzyme active site. While the central domain is similar to that of all the other amylase family enzymes, branching enzyme shares the structure of all three domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 37 publications
4
116
0
Order By: Relevance
“…Analysis of SBE primary sequences indicates that SBEs belong to the a-amylase superfamily of enzymes (termed the glycoside hydrolase family 13 [GH13]) and structurally made up of three domains: a central (b/a)-barrel catalytic domain, or A-domain, an NH 2 -terminal domain, and a C-terminal domain (58,59). The central catalytic domain is highly conserved among the members of the a-amylase (GH13) superfamily, and only isoamylases share all three domains with the BEs and are able to bind sugars in the a-1,6-position (59).…”
Section: Structure-function Relationships Of Sbesmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of SBE primary sequences indicates that SBEs belong to the a-amylase superfamily of enzymes (termed the glycoside hydrolase family 13 [GH13]) and structurally made up of three domains: a central (b/a)-barrel catalytic domain, or A-domain, an NH 2 -terminal domain, and a C-terminal domain (58,59). The central catalytic domain is highly conserved among the members of the a-amylase (GH13) superfamily, and only isoamylases share all three domains with the BEs and are able to bind sugars in the a-1,6-position (59).…”
Section: Structure-function Relationships Of Sbesmentioning
confidence: 99%
“…The sequences of the NH 2 -and C-terminal domains are highly variable, but nevertheless jointly contribute to catalytic activity with the Adomain. Various experimental approaches (discussed in the sections below) have been used to deduce the functions of the three domains of SBE, including analysis of amino acid sequence alignments, site-directed mutagenesis (60), domainswapping experiments (12), and utilizing available X-ray crystallographic structures (59,61,62).…”
Section: Structure-function Relationships Of Sbesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to GBD represented by the β-subunit of the mammalian AMP-activated protein kinase (AMPK) (Polekhina et al 2005), the family CBM48 contains the putative SBDs present in the four enzyme specificities from the α-amylase enzyme family: pullulanase (PUL), isoamylase (IAM), maltooligosyl trehalohydrolase (MOTH), as well as the glycogen branching enzyme (GBE) and the starch branching enzyme (SBE). These enzymes have recently been revealed to constitute the so-called GH13 PUL subfamily (Janecek et al 2007); the SBD being found as a domain that precedes the catalytic (β/α) 8 -barrel (Katsuya et al 1998;Feese et al 2000;Abad et al 2002;Mikami et al 2006). Within the CAZy classification, these enzymes have been grouped in subfamilies as follows: GBE and SBE (GH13 8, GH13 9), MOTH (GH13 10), IAM (GH13 11) and PUL (GH13 12,GH13 13,GH13 14).…”
Section: Introductionmentioning
confidence: 99%
“…The only exception is represented by the ␤-subunit of AMPK (37), which showed that CBM48 is a separate domain that binds cyclodextrin to increase its binding ability for the glucosyl polymeric structures commonly found in glycogen (62). Despite the wealth of structural information on CBM48 (36,52,55,(63)(64)(65)(66)(67) (for a review, see Ref. 68)), this paper is, to the best of our knowledge, the first to demonstrate that an independent CBM domain folds to interact with the catalytic domain and participates in substrate binding at the active site.…”
Section: Discussionmentioning
confidence: 99%